1985
DOI: 10.1116/1.572862
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten carbide phase transformation during the plasma spray process

Abstract: Tungsten carbide coatings applied by the plasma spray process have been widely used in wear applications. In the W–C–Co ternary system, tungsten carbide can either be present as WC or W2C. Frequently WC transforms into W2C during the plasma spray process. In this study, tungsten carbide/17% cobalt coatings were applied by both the air plasma and the vacuum plasma spray processes using different power levels and plasma gases. The W2C phase was found by X-ray diffraction techniques in the air plasma sprayed coat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This situation leads to an excessive level of material degradation in form of oxidation, decomposition and decarburization which would affect the wear performance of the resulting coating (Ref 20,79). It has been reported that a large portion of the WC phase can transform into W 2 C phase during the plasma spray process (Ref 12,105). Results from a study by Al-Mutairi et al (Ref 106) show that excessive phase transformation and cobalt evaporation occur during APS as compared to HVOF, which causes the wear performance of WC-based coatings processed by APS to be inferior compared to those sprayed using HVOF (Ref 107 -110).…”
Section: Ni-based Alternatives Processed By Thermal Spraymentioning
confidence: 99%
“…This situation leads to an excessive level of material degradation in form of oxidation, decomposition and decarburization which would affect the wear performance of the resulting coating (Ref 20,79). It has been reported that a large portion of the WC phase can transform into W 2 C phase during the plasma spray process (Ref 12,105). Results from a study by Al-Mutairi et al (Ref 106) show that excessive phase transformation and cobalt evaporation occur during APS as compared to HVOF, which causes the wear performance of WC-based coatings processed by APS to be inferior compared to those sprayed using HVOF (Ref 107 -110).…”
Section: Ni-based Alternatives Processed By Thermal Spraymentioning
confidence: 99%
“…A detailed and excellent analysis of the decomposition and oxidation of a WC-Co powder in a controlled atmosphere plasma spray process (argon) was performed by Lammer and Benesovsky. 12 Other attempts to exclude the negative influence of the atmosphere used vacuum plasma spraying (VPS), 13,14 but the negative effect of high temperature remained. Despite these measures, the quality of DGS hardmetal coatings was never attained with plasma spray processes.…”
Section: Some Historical Pointsmentioning
confidence: 99%
“…Plasma spraying is one of these techniques and differs from others by the formation of its heat source. The plasma gun dates back to the mid 1950s, when it was introduced for the deposition of alloys and ceramics (22). Since then, equipment improvements, process knowledge, diagnostic techniques and novel coating materials have expanded the applications of plasma spraying.…”
Section: Plasma Sprayingmentioning
confidence: 99%
“…Perhaps the most well-known case is the decarburization of WC powders during air plasma spraying (22,23). Similar reactions leading to mass loss have been observed in spraying other refractory metal carbides (27).…”
Section: Coating Chemistrymentioning
confidence: 99%
See 1 more Smart Citation